E-Module Design Based on STEM and RME for Student Numeracy Development in Senior High Schools: Insights from a Needs Analysis - Saputri, Veni; Kusumah, Yaya Sukjaya; Turmudi, Turmudi; Al Jupri, Al Jupri (Proceedings of International Conference on Science, Education, and Technology, 2025)
This study aims to analyse the needs of students and teachers in developing e-modules for mathematics learning based on the STEM (Science, Technology, Engineering, and Mathematics) and RME (Realistic Mathematics Education) approaches. This study used a descriptive approach with 203 students and 6 mathematics teachers from several high schools in Bekasi City as subjects. Data were collected through four types of instruments, namely numeracy tests, student needs questionnaires, teacher needs questionnaires, and semi-structured interviews. Data analysis was conducted using the Miles & Huberman model, which includes the stages of data collection, data reduction, data presentation, and conclusion drawing. The results of the analysis showed that the students had difficulties in understanding the material, performing calculation operations, and solving mathematical problems. The students also show low self-efficacy and require contextual, interesting, and interactive teaching materials. The students' preferences for the appearance of the e-module include the use of colours that are not excessive, consistent fonts, simple navigation, and communicative language. On the other hand, teachers show a limited understanding of the STEM-RME approach and have not fully integrated the approach into learning. The teachers express the need for learning strategies and media that can improve students' numeracy and self-efficacy, and emphasise the importance of training in the use of digital media. These findings provide an important basis for designing e-modules that meet the requirements and characteristics of users, namely students and teachers, to support the effectiveness of mathematics learning.